Immune characterization and expression analysis of a goose-type lysozyme gene from Pinctada fucata martensii - Guo, Zhijie; Shen, Chenghao; Liang, Haiying; Zhang, Meizhen; Liang, Bidan; Zhang, Bin (Frontiers in Marine Science, 2022)
In the present study, a g-type lysozyme was successfully screened and cloned from Pinctada fucata martensii (designated as PmlysG). The cDNA has a length of 973 bp with an open reading frame (ORF) of 769 bp, encoding a protein with 255 amino acids. Quantitative real-time PCR (qRT-PCR) detected PmlysG transcript in multiple tissues, with the highest expression being in the hepatopancreas. Furthermore, qRT-PCR detected temporal expression of PmlysG mRNA in the hepatopancreas after in vivo stimulation with pathogen-associated molecular patterns (PAMPs), such as LPS, PGN and PolyI:C. Although PmlysG responded to all three stimulation modes, it quickly responded to PGN stimulation. The recombinant protein of g-type lysozyme of P.f. martensii (rPmlysG) was used for antibacterial function analysis. Results showed that rPmlysG has antibacterial function against Vibrio parahaemolyticus, Aeromonas hydrophila, and Pseudomonas aeruginosa. These data suggest that the identified PmlysG participates in the innate immune responses of P.f. martensii against pathogen infection.